Contribution of urban functional zones to the spatial distribution of urban thermal environment - Chen, Yang; Yang, Jun; Yang, Ruxin; Xiao, Xiangming; Xia, Jianhong (Cecilia) (Building and environment, 2022)
With the accelerated rate of urbanization, reasonable identification of urban functional zones has been increasingly important to urban development. In this study, we used OpenStreetMap and point of interest data combined with the classification standard of urban construction land, to identify the urban functional zones. In addition, Landsat 8 remote sensing images were utilized to retrieve land surface temperature, and the random forest algorithm was used to evaluate the contribution of different types of urban functional zones to the urban thermal environment. The results showed that the land surface temperature along Hunhe River in the central area of Shenyang gradually decreased. The temperature was high in the center of the experimental area and low in the north and south. Furthermore, in the main city zone of Shenyang, single functional zones accounted for 65.71% of the total study area, whereas mixed functional zones accounted for 34.29%. Among the various types of urban land, public service facility land contributed the most to the urban thermal environment with an impact of 21.65%, followed by residential, industrial, and commercial service facility lands, with impacts of 19.89%, 18.44%, and 17.58%, respectively. Additionally, the impact of road traffic land was 14.92%, whereas that of green square land was the lowest at 7.51%, 14.14% lower than that of public service facility land. [Display omitted] •Analyzes the spatial distribution heterogeneity of the surface thermal environment in the main area of Shenyang.•Analyzes the spatial structure of the main area of Shenyang based on functional zoning.•Analyzes the spatial interaction between various urban spatial activities and the surface thermal environment.•Calculates the contribution of different types of urban functions to the urban thermal environment.